1986
DOI: 10.1037/0278-7393.12.4.575
|View full text |Cite
|
Sign up to set email alerts
|

Meaning, sound, and syntax: Lexical priming in sentence production.

Abstract: Theories of sentence production based on speech errors divide lexical-syntactic integration processes into two components. The first involves formulating an abstract structural representation that includes semantically specified lexical items. The second involves placing phonologically specified content words into a syntactic frame whose configuration is determined by the initial structural representation. Syntactic form thus may be influenced directly by variations in the semantic processing of words, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
191
0
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(201 citation statements)
references
References 56 publications
7
191
0
3
Order By: Relevance
“…Ad hoc categories, lacking that lexical link, therefore do not show Kelly et al (1986), that typicality did not influence choice of a constituent as subject or object? Given that syntactic, sentence-level ordering seems not to be strongly influenced by lexical form (Bock, 1986), the lexical account is consistent with their null result. However, null results may always be due to a failure to find the correct experimental conditions to reveal the effect.…”
supporting
confidence: 73%
“…Ad hoc categories, lacking that lexical link, therefore do not show Kelly et al (1986), that typicality did not influence choice of a constituent as subject or object? Given that syntactic, sentence-level ordering seems not to be strongly influenced by lexical form (Bock, 1986), the lexical account is consistent with their null result. However, null results may always be due to a failure to find the correct experimental conditions to reveal the effect.…”
supporting
confidence: 73%
“…The latter strategy has the advantage that it reduces the latency to begin the housekeeping chores, and it allows planning and execution to take place in parallel. Similarly, as Bock has argued (Bock, 1986(Bock, , 1987a(Bock, , 1987bBock, Loebell, & Morey, 1992), if the sentence production system places the most available concept into an early sentence position, speaking can begin while the rest of the sentence is being planned. If the discourse production system begins descriptions with easier material, the work of planning the more difficult material can be carried out in parallel with articulation.…”
Section: Discussionmentioning
confidence: 95%
“…Recent work in language production has uncovered some ofthe processes underlying decisions about word order in sentences. For example, Bock and colleagues (Bock, 1986(Bock, , 1987a(Bock, , 1987bBock & Warren, 1985;Kelly, Bock, & Keil, 1986) have shown that words that are frequent, prototypical, concrete, or semantically primed tend to take earlier positions in a sentence. Ferreira (1994) has demonstrated that thematic roles such as agent and experiencer tend to be subjects and that roles such as theme and patient tend to be objects.…”
mentioning
confidence: 99%
“…In accord with this, context can affect sentence formulation in monologue, so that a focused phrase is produced first (Bock 1986a;Prat-Sala & Branigan 2000). Prat-Sala and Branigan, in particular, found effects of focus on word order that were not due to differences in grammatical role.…”
Section: Producing Words and Sentencesmentioning
confidence: 92%